2014
DOI: 10.11648/j.ijnfs.20140305.16
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Total Aflatoxins Level of Two Major Nuts Consumed in Makurdi Benue State, Nigeria

Abstract: Abstract:The main aim of this study was to determine the total aflatoxin (TAF) contents of roasted cashew nuts (Anacardium occidentale), and the roasted, hulled and dehulled groundnuts (Arachis hypogaea L.) sold and consumed in the major public areas of Makurdi Benue State, Nigeria. The items were sampled from 10 different locations based on human traffic densities and sellers of the product and then analysed for TAF contents using direct competitive Enzymelinked Immunosorbent Assay (ELISA) method. In the roas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
13
1
1
Order By: Relevance
“…They detected levels of 5.92 -11.02 μg/kg. A study by Ubwa et al [22] evaluated the total aflatoxin levels of roasted, hulled, and dehulled groundnuts from markets in Makurdi and observed that dehulled groundnuts had aflatoxin levels of between 1.50 ppb to 20.00 μg/kg. However, Vabi et al [23] determined AFB 1 levels in groundnuts and groundnut-based products produced across five Northwestern states and also in Benue state, and observed AFB 1 concentrations of 7.82 and 12.33 μg/kg 10.15 μg/kg in Benue State respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They detected levels of 5.92 -11.02 μg/kg. A study by Ubwa et al [22] evaluated the total aflatoxin levels of roasted, hulled, and dehulled groundnuts from markets in Makurdi and observed that dehulled groundnuts had aflatoxin levels of between 1.50 ppb to 20.00 μg/kg. However, Vabi et al [23] determined AFB 1 levels in groundnuts and groundnut-based products produced across five Northwestern states and also in Benue state, and observed AFB 1 concentrations of 7.82 and 12.33 μg/kg 10.15 μg/kg in Benue State respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the supernatant was filtered through a Whatman No. 1 filter paper then the filtrate was collected [23][24][25].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Deteksi aflatoksin B1 menggunakan metode ELISA (Enzyme-Linked Immunosorbent Assay) -AgraQuant Aflatoxin assay merujuk pada Ubwa et al, 2014…”
Section: Kandungan Aflatoksin B1unclassified